Al-Tāsāmuḥ al-Islāmī fī al-Futūḥāt al-Islāmiyyah; Fatḥ Miṣr Namūdzaj - Mukhamad Hadi Musolin Subagio; Rido Uwais Hasan Surur (Universitas Islam Negeri Ar-Raniry, 2020)
The story of the Islamic conquest of Egypt is one of the most exciting episodes of Egyptian history. Not because of the events and battles that accompanied the conquest, but rather because of the enormous effects and developments that have resulted in the history of Egypt and its people in terms of religion, language, culture, etc. As for the march of conquest, the conduct of armies, and the war against the soldiers, they were subjected to many statements by historians, and there were conflicting reports about the conquest of Egypt, and was this conquest reconciled with a covenant, or by force? The way Egypt was conquered went in a way that contrasts with its conquests in the City of Shams and others. Also, the march of opening Egypt was subjected to multiple suspicions and myths that have no basis, some were able to attach to the history of the Islamic conquests of Egypt, but Allah defended the conquests through the writings of Muslim and non-Muslim scholars. This paper comes to reveal aspects of greatness in Islamic tolerance with the Christians of Egypt, which was their main reason for converting to Islam. This study used the historical, critical and analytical method to present facts and discuss ideas. Among the most important results: the proof of tolerance in theory and in reality concerning the conquest of Egypt, the conversion of Egyptians to Islam because of its grace and ease, and rejecting the myth of the march of the Islamic conquest of Egypt from the beginning to the end.